CONTENT AND ESSENCE OF AUTHORITIES AND TASKS OF THE NATIONAL GUARD OF UKRAINE WHEN PERFORMING FUNCTIONS TO ENSURE STATE SECURITY - Trotskyi, Ruslan; Kurilo, Oleh (Honor and Law, 2023)
The article analyzes the content and essence of the powers and tasks of the National Guard of Ukraine in the performance of functions to ensure state security, gives a number of theoretical-legal and practically oriented arguments relating to the direct organization of the National Guard of Ukraine’s activities in this direction. The author substantiates that the activity of the National Guard of Ukraine in terms of ensuring the rights and freedoms of a person and a citizen, in particular in the way of repelling armed aggression of Russia against the independence and territorial integrity of Ukraine, is fundamental, but the scope of powers and, accordingly, the tasks defined by the legislation of Ukraine, which are formed on fulfillment of the strategic goal requires improvement and additions. It is noted that the powers of the National Guard of Ukraine, formulated in the Law of Ukraine "On the National Guard of Ukraine", are first of all supplemented by industry legislation, and the conditions for repelling armed aggression and countering occupation forces formulate a new legal dimension of the relevant context, supplementing the range of normative and legal instruments regulating the activities of the National Guard of Ukraine, as well as decisions of the National Security and Defense Council of Ukraine. At the same time, the function of ensuring state security, being institutionally attributed to the competence of the Security Service of Ukraine, is fragmentarily reflected and clearly indicated in the legislation regulating the activities of the National Guard of Ukraine, and the structure and content of the activities of individual units of the National Guard of Ukraine direct the vector of state activity through the prism of the activities of this military formation with law enforcement functions in the single direction of ensuring the security of the state and the rights and freedoms of its citizens. The perspective of further scientific research lies in the need to determine the basis of the interaction of the National Guard of Ukraine with other subjects of the security and defense sector of Ukraine in the context of ensuring the state security of Ukraine.